2022
DOI: 10.1186/s12882-022-02672-3
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact of blood pressure on neurological symptoms and the risk of ESKD in primary and secondary thrombotic microangiopathies based on clinical presentation: a retrospective study

Abstract: Background The impact of blood pressure on neurological symptoms and risk of end-stage kidney disease (ESKD) is unknown in primary and secondary thrombotic microangiopathies (TMAs). Methods We measured baseline systolic (SBP) and diastolic (DBP) BP in consecutive 563 patients with adjudicated primary and secondary TMAs, and assessed its association with the risk of ESKD. Results Normal BP, grade 1, 2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Patients with TTP often do not have hypertension at presentation. A retrospective study done in France on 564 patients with TMA showed that normal BP or grade 1 hypertension (140-159/90-99 mmHg) was found in most patients with TTP [7]. Our first patient had a typical HTN-TMA presentation with history of hypertension and ECG changes suggestive of left ventricular hypertrophy.…”
Section: Discussionmentioning
confidence: 67%
“…Patients with TTP often do not have hypertension at presentation. A retrospective study done in France on 564 patients with TMA showed that normal BP or grade 1 hypertension (140-159/90-99 mmHg) was found in most patients with TTP [7]. Our first patient had a typical HTN-TMA presentation with history of hypertension and ECG changes suggestive of left ventricular hypertrophy.…”
Section: Discussionmentioning
confidence: 67%
“…In the latter situation, patients usually presented with severe/malignant hypertension. It is presently unknown whether severely elevated blood pressure is evidence of extensive parenchymal damage associated with TMA or may play a role in the development of TMA in transplanted and nontransplanted populations [ 3 , 31 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 69 ] TMA syndromes and hypertension (HTN) are linked, and HTN severity in TMA correlates with poor outcomes. [ 70 ] Glomerular ischemia caused by the microvascular capillary blockage in the glomeruli and other kidney tissues is the most likely mechanism through which TMA causes HTN. [ 71 ] Patients who take gemcitabine have a risk of developing new or worsening HTN.…”
Section: Cancer Complications Cause Renal Injurymentioning
confidence: 99%